Development of HLA-modified induced pluripotent stem cell-derived dendritic cells for a novel cancer immunotherapy. Issue 5 (September 2022) - Kojima, Taku; Yuno, Akira; Hirayama, Masatoshi; Fukuma, Daiki; Shinohara, Masanori; Nishimura, Yasuharu; Nakayama, Hideki
Abstract: Objectives: We previously established a method to generate a human iPS cell-derived myeloid cells (iPS-MLs) from a human leukocyte antigen (HLA)-A *24:02 donor, which could differentiate into dendritic cells (DCs) and had a high potential in stimulating T cells. However, for clinical applications, the histoincompatibility between iPS cells and cells in cancer patients has remained as a key challenge. One solution is to construct the iPS cell library covering all HLA haplotypes, but it is excessively laborious and impractical. In order to overcome this problem, we generated HLA-modified iPS cells to avoid immune rejection. Methods: We disrupted HLA-A, -B and DRA genes by using a CRISPR-Cas9 system and subsequently introduced HLA-A *02:01 into iPS-MLs. We examined the immunogenic capacities of these HLA-deficient iPS-MLs for inducing antigen-specific CD8 + T cells derived from an allogeneic donor. Results: HLA-deficient iPS-MLs could avoid recognition by alloreactive CD8 + T cells. HLA-deficient iPS-MLs with introduced HLA-A *02:01 differentiated into functional DCs upon stimulation with IL-4, and induced HLA-A2-restricted melanoma antigen recognized by T cells-1 (MART)−1-specific CD8 + T cells derived from an allogeneic donor. Furthermore, HLA-deficient iPS-MLs with introduced HLA-A *02:01 and MART-1 could induce HLA-A2-restricted MART-1-specific CD8 + T cells derived from an allogeneic donor. Conclusion: We developed a method that can exchange HLA alleles from HLA-A *24:02 to* 02:01 in iPS-MLs, and our findings may overcome the obstacle of histoincompatibility in DC vaccination therapy, regardless of HLA allele.